Stress priming enhances drought response in Sorghum bicolor potentially involving PIP2;5 - Pegorin, Priscila [UNESP]; Rabelo Schley, Thayssa [UNESP]; Rossini, Bruno César [UNESP]; Araújo Júnior, João Pessoa [UNESP]; de Almeida, Luiz Fernando Rolim [UNESP] (Springer Nature, 2025)
Stress priming, the exposure to an initial stressor, can positively affect a plant’s response to subsequent stresses. Drought priming can induce genetic, biochemical, and physiological responses that enable plants to store information, initiating a memory process that enhances their responsiveness to future drought events. Aquaporin regulation could be among these responses because they have been related to water deficit tolerance. We characterized the physiological drought priming in adult leaves of Sorghum bicolor (L.) Moench, and analyzed its relationship with PIP2;5 aquaporin. Plants were subjected to two events of severe progressive water deficit (SPWD) followed by rehydration. Water status, photosynthesis, antioxidant system, and PIP2;5 expression were analyzed. The data were collected on the first day of the experiment, during the water deficit events, and at 24 and 72 h after each rehydration. SPWD plants showed improved values of relative water content (RWC), leaf water potential, transpiration (E), stomatal conductance (gs), lipid peroxidation, and H2O2 concentration during the second event of water deficiency and rehydration compared to the first stress cycle. This suggests that sorghum promoted physiological responses to increase water deficit tolerance, e.g. strategies in the water-use economy, evidencing the priming of drought stress. Additionally, PIP2;5 was downregulated during the water deficit period and immediately upregulated when rehydration was applied. Aquaporin regulation during the second stress event was positively correlated to RWC, water use efficiency, intrinsic water use efficiency, and leaf area, which might indicate that PIP2;5 can impact water status, gas exchange, and growth responses of S. bicolor to recurrent SPWD periods.
Keywords: Physiological stress recovery; Physiological stress response; Plasma membrane intrinsic protein; Stress sign; Water stress